UPAYA PONDOK PESANTREN DALAM MENGATASI KURANGNYA PARTISIPASI MASYARAKAT TERHADAP PENGEMBANGAN PENDIDIKAN ISLAM - Hasanah, Uswatun; Kustati, Martin; Amelia, Rezki; Zalnur, Muhammad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
Islamic boarding schools are one of the implementers of Islamic education activities that are expected to be able to build and develop them together with the community. This is done for the advancement of Islamic education itself. Therefore, it is natural that the community demands that madrassas be better in terms of their performance which should put the essence of Islamic education as a priority in its implementation. The purpose of this study is to examine juridically and philosophically the policies that regulate how the efforts of Islamic boarding schools in overcoming the lack of community participation in the development of Islamic Islamic education. This research uses a qualitative approach carried out in the field (field research) by analyzing efforts and obstacles to community participation. From this research, it was obtained that by involving the community in various programs in Islamic boarding schools that are social in nature, Islamic boarding schools can communicate with the community through religious values, and hold regular meetings once a month with the community discussing the management of Islamic boarding schools. The obstacles faced by the community are busy work, lack of information about the madrasah program, and the lack of knowledge of most people about the importance of participation.